Chemical Heroes : Pharmacological Supersoldiers in the US Military - Bickford, Andrew (Global Insecurities, 2020)
In Chemical Heroes Andrew Bickford analyzes the US military's attempts to design performance enhancement technologies and create pharmacological "supersoldiers" capable of withstanding extreme trauma. Bickford traces the deep history of efforts to biologically fortify and extend the health and lethal power of soldiers from the Cold War era into the twenty-first century, from early adaptations of mandatory immunizations, to bio-protective gear, to the development and spread of new performance enhancing drugs during the global War on Terror. In his examination of the government efforts to alter soldiers' bodies through new technologies, Bickford invites us to contemplate what constitutes heroism when armor becomes built in, wired in, even edited into the molecular beings of an American soldier. Lurking in the background and dark recesses of all US military enhancement research, Bickford demonstrates, is the desire to preserve US military and imperial power.